THE IMPORTANCE OF PUBLIC-FUNDED CHARGING STATIONS TO INCREASE THE RATE OF ELECTRIC VEHICLE (EV) OWNERSHIP IN INDONESIA - Faiz Rafiza Ahmadani; Rafi Aquary (Sociae Polites, 2021)
The current surplus of electricity across Indonesia has further underlined many opportunities to optimize the usage of electricity in many sectors; including on the issue of Electric Vehicle (EV) ownership within the country. According to the government’s projection, the state-owned enterprise (SOE) of PLN would construct 254.181 units of charging stations by 2030. However, there exists the problem of ‘chicken and egg’; in which more EV charging stations would be required to spur EV sales and vice versa. In addition to that, the lack of charging stations has also led to the disinterest from the public to purchase EVs due to fear of range anxiety. Hence, this paper is written to address the importance of publicly funded charging stations in Indonesia to help cultivate EV development within the country. Not only that, since Indonesia is the largest member country of ASEAN, it could be the ‘trendsetter’ of this issue in the region and would have the upper hand position as an early adopter. Our hypotheses suggest that not only publicly funded the development of charging stations would be beneficial to the future-buyer of EV, but also for the government itself. Keywords: Electric Vehicle, Charging Station, Public-Funded, Range Anxiety